Map of Ontario and Quebec [1905] - Sydney A. Fisher (Producer)
A map of Ontario and Quebec issued by the Minister of Agriculture in 1905. Includes railway routes, ferry or steamship routes, bodies of water, towns and cities. Counties in Ontario and Quebec are outlined with hashed lines. Where counties are too small to be labelled with letters, they are numbered with a key towards the bottom of the map. Scale is ca. 1 : 4,600,000. Map shows Keewatin (now part of Nunavut), Ungava (now Quebec and Labrador), New Brunswick, Nova Scotia, Prince Edward Island, and parts of the United States, though none of these areas have as much detail as Ontario and Quebec. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .